Dispute Resolution Mechanism in Buying and Sale Transactions Conducted in E-Commerce - Suisno; Sastradinata, Dhevi Nayasari; Afrida, Nabila (Universitas Islam Lamongan, 2024)
ABSTRACT The advancement of information technology today provides freedom of distance, space and time to improve human performance in various activities, thereby increasing productivity and efficiency. People also use this technology as a source of income in their spare time, as entrepreneurs and consumers who offer goods and services through electronic media connected via the Internet. With the development of information flow and increasingly sophisticated digital technology, as well as the increasing use of mobile devices, this has led to changes in consumer behavior. Many people are starting to use online stores. The use of technology and information through online media in business is known as online buying and selling. The nature of the investigation itself is to obtain the truth based on the actual facts. This research method uses a normative legal research method, with a statutory approach and a conceptual approach. The legal materials used are primary legal materials including: the Law Code from the results of the research it can be concluded that: if a dispute occurs in a buying and selling transaction via the internet, it can basically be done through the courts (litigation) or outside the courts (non-litigation) such as Negotiation, Mediation and Arbitration. However, in general, the disputing parties will be more inclined to resolve the dispute through non-litigation channels because the costs are relatively cheap, decisions can be made in a relatively short time, and the force of the decision is the same as a court decision which is final and binding.